2015
DOI: 10.18502/ken.v1i1.339
|View full text |Cite
|
Sign up to set email alerts
|

Aerated Underbalance Drilling Screening Assessment at “X” Geothermal Field

Abstract: Fault network is a challenging problem for geothermal drilling operations. Formation fluid contains high temperature production fluid which can reach >225 o C on high enthalpy system. The other consequences is that almost all fault network has low pressure or subnormal pressure. This low pressure results to a loss circulation problem. This low pressure can even go lower if the geothermal field has been exploited for a long period. A miss reservoir management, that do not re-inject sufficient amount of fluid, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The CDE bit delivered more drilled interval at a higher ROP while providing a smooth, high-quality wellbore compared with the offset well that drilling with TCI bits in Philippines geothermal well construction [20].The new CDE bits also showed about 29% increase in footage than traditional PDC bits, but a slight ROP declined in in hard-rock geothermal applications, in California [21]. Due to the existence of reservoir fracture, massive losses including partial and total losses was the another challenge to drill the geothermal well [22].Usually, the targets of wells in geothermal drilling are faults, fractures or fissures that have high permeability and are connected with the geothermal reservoir. Loss of circulation in drilling operations causes poor cleaning of cuttings, low penetration rates, increasing the risk of drillstring stuck, increasing the consumption of drilling fluid materials, reducing the productivity of the well.…”
Section: Introductionmentioning
confidence: 99%
“…The CDE bit delivered more drilled interval at a higher ROP while providing a smooth, high-quality wellbore compared with the offset well that drilling with TCI bits in Philippines geothermal well construction [20].The new CDE bits also showed about 29% increase in footage than traditional PDC bits, but a slight ROP declined in in hard-rock geothermal applications, in California [21]. Due to the existence of reservoir fracture, massive losses including partial and total losses was the another challenge to drill the geothermal well [22].Usually, the targets of wells in geothermal drilling are faults, fractures or fissures that have high permeability and are connected with the geothermal reservoir. Loss of circulation in drilling operations causes poor cleaning of cuttings, low penetration rates, increasing the risk of drillstring stuck, increasing the consumption of drilling fluid materials, reducing the productivity of the well.…”
Section: Introductionmentioning
confidence: 99%
“…This technology allows drilling at abnormally low reservoir pressure (ALRP) with catastrophic levels of drilling fluid absorption due to high permeability or the presence of large filtration channels -cracks and cavities, as well as under a combination of these conditions. Various cases of using aerated solutions have shown that they really allow more efficient removal of cuttings from the bottom of wells [2], as well as contribute to the elimination of the resulting sticking.…”
Section: Introductionmentioning
confidence: 99%